Energy from Waste: Generation Potential and Mitigation Opportunity - Francesco Bosello; Lorenza Campagnolo; Fabio Eboli; Ramiro Parrado (Fondazione Eni Enrico Mattei (FEEM), 2014)
The present research proposes a macroeconomic assessment of the role of waste incineration with energy recovery (WtE) and controlled landfill biogas to electricity generation and their potential contribution to a CO2 emission reduction policy, within a recursive-dynamic computable general equilibrium model. From the modelling viewpoint, introducing these energy sectors in such a framework required both the extension of the GTAP7 database and the improvement of the ICES production nested function. We focus our analysis on Italy as a signatory of the GHG reduction commitment of 20% by 2020 wrt 1990 levels proposed by the European Community; the rest of the world is represented by 21 geo-political countries/regions. It is shown that albeit in the near future WtE and landfill biogas will continue to represent a limited share of energy inputs in electricity sector (in Italy, around 2% for WtE and 0.6% for biogas in 2020) they could play a role in a mitigation policy context. The GDP cost of the EU emission reduction target for the Italian economy can indeed be reduced by 1% when the two energy generating options are available. In absolute terms, this translates into an annuitized value of 87-122 million exteuro.
Keywords: C68; E27; Q42; Q43; Q54; 330; Climate Change; Mitigation; Energy From Waste